2012
DOI: 10.1002/jcc.22931
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic model for photoinduced anisotropy

Abstract: We present a stochastic model for the kinetics of photoinduced anisotropy in a sample of molecular chromophores that may undergo photoisomerization. It is assumed that the chromophores do not interact among them, but are embedded in a medium that slows down the rotational diffusion. The model makes use of data about the photoinduced reorientation of the single chromophore, its photoisomerization and its rotational diffusion, that are made available by molecular dynamics simulations. For the first time such mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(82 citation statements)
references
References 27 publications
5
77
0
Order By: Relevance
“…Overall, the virtually barrierless decay path to the CI, which involves a switch from the ππ* to the nπ* state, is consistent with the identification of two time constants ( τ 1 and τ 2 ) in the subpicosecond range and the early appearance of the transient absorption around 600 nm, tentatively assigned to the ground‐state cis minimum. Our mechanistic picture that involves mainly rotation is also consistent with the one described for other azobenzene derivatives, such as the parent azobenzene or recently synthesized phenylazoindoles …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, the virtually barrierless decay path to the CI, which involves a switch from the ππ* to the nπ* state, is consistent with the identification of two time constants ( τ 1 and τ 2 ) in the subpicosecond range and the early appearance of the transient absorption around 600 nm, tentatively assigned to the ground‐state cis minimum. Our mechanistic picture that involves mainly rotation is also consistent with the one described for other azobenzene derivatives, such as the parent azobenzene or recently synthesized phenylazoindoles …”
Section: Resultssupporting
confidence: 88%
“…Similar dynamics with 3–4 time constants in the femto‐ and picosecond range have been described for push–pull‐substituted derivatives . Regarding the mechanism, recent theoretical studies favor isomerization through the torsional mechanism …”
Section: Resultssupporting
confidence: 70%
“…The latter effect can be partially mitigated using socalled decoherence corrections; the interested reader is referred to the according literature. [132,[136][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153] Tunneling effects can also not be described with surface hopping although there exist several approaches to alleviate this deficiency, see, for example, Refs. [154][155][156][157][158].…”
Section: Dynamics Simulations Of Intersystem Crossingmentioning
confidence: 99%
“…8 hops up to the S 3 state at 0.5 fs, back to the S 2 state via CI-rot S 2 /S 3 at 21.0 fs, down to the S 1 state via CI-cis S 1 /S 2 at 21.5 fs, and finally down to the S 0 state via CI-rot S 0 /S 1 at 53.0 fs. Based on the semiempirical nonadiabatic molecular dynamics simulation including solvent and decoherence effect, Persico and coworkers 13,28,29 have proposed that for the pp* isomerization mechanism the torsion motion of NQN bond plays a very important role in both vacuum and solvent environments. A typical reactive trajectory shown in the right panel of Fig.…”
Section: Photoisomerization Mechanisms Starting From S 2 Statementioning
confidence: 99%
“…In the hybrid theoretical and experimental investigation performed by Schultz et al, 23 the direct ab initio molecular dynamics with the complete active space self-consistent field (CASSCF) method was used to demonstrate the initial stage dynamics of transazobenzene after pp* excitation. Persico and coworkers 13,28,29 carried out massive trajectory surface-hopping simulations based on the semiempirical floating occupation of molecular orbital configuration interaction (FOMO-CI) methods with or without OPLS force fields for cis-and trans-azobenzene photoisomerization followed by both np* and pp* excitation, and they found that both the transcis and cistrans photoreactions are induced by the torsion pathway of the NQN bond combined with torsion of the N-C bonds. Sauer et al 25 and Dou and coworkers 26,27 performed semiclassical electron-radiation-ion dynamics (SERID) simulations with time-dependent density functional methods, and found unusual results in which the torsion mechanism dominates the isomerization processes for both cis-and transazobenzene followed by pp* excitation.…”
Section: Introductionmentioning
confidence: 99%